PENERAPAN PSAK NO 14 ATAS PERSEDIAAN BARANG DAGANG (STUDI KASUS PADA PT. ASIA TENGGARA MURNI) - Palar, Royke; Pontoh, Winston; Pinatik, Sherly (Universitas Sam Ratulangi, 2020)
Inventories are an important active on a trading company, because it is one of component that is very active. A company in its day to day normal activities will prioritize the conversion of inventories to cash, and also to obtain profit from the margin between Cost of Goods Sold (COGS) and the product selling price. It should be known that inventories are vulnerable to product faults and thievery, damaged in store, invalid entries, invalid demand registries, items that does not match the order and other possibilities that may cause a difference on inventories on the ledger and the actual inventories on the warehouse. One to its importance, inventories has to be managed properly in accordance with the Accounting Standard that is implemented in Indonesia. The purpose of this research is to know whether or not the implementation of Inventories Accounting in PT. Asia Tenggara Murni are being implemented in accordance with PSAK 14, using descriptive analysis method, the research shows that the inventories Accounting method in PT. Asia Tenggara Murni has been implemented in accordance with PSAK No.14 which consists of recording, appraising, and full disclosure of inventories.